Pengaruh Perputaran Kas, Perputaran Piutang dan Perputaran Persediaan Terhadap Laba Bersih pada Industri Otomotif yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2017 - Kms Muhammad Jauharul Wathon (Science of Management and Students Research Journal (SMS), 2020)
fistly, this research to analyse how to analyse the effectof the cash turnover, receivables turover and inventories turnover are simultaneously on net profit on automotive industry which is listed on the stock market. Second, effect of the cash turnover, receivables turover and inventories turnover are partial on net profit on automotive industry which is listed on the stock market.The research methodology is descriptive and quantitative analysis methods. Data used is secondary data. The population become object in this research is automotive industries period of year of 2013-2017. Amount sample the used is the six (6)  industry company and still stand up during period of perception and also publicized of year of 2013-2017 by Indonesian Stock Exchange the analysis multiple regression, hypotesis test so determinant coefficient F test  and  t test.The object of this research is automotive industries listed on the Stock Exchange Indonesia 2013-2017. The sampel in the receach is PT Astra International,Tbk (ASII),  PT Astra Otopart,Tbk (AUTO), PT Indo Korda,Tbk (BRAM), PT Indospring,Tbk (INDS), PT Nipress,Tbk (NIPS) and PT Selamat Sempurna,Tbk (SMSM).Results of multiple regression equation is Y = 11,528  -  0,556X1  -  1,423X2  +  3,158X3   + e,  F test result, it is known that Perputaran kas, Perputaran Piutang, NetProfit Margin and Perputaran Persediaans simultaneously significant effect on Stock Prices. F count larger than F table (37,372 > 2,086) or comparing the significant level of 0.05 then (0.000 < 0.05) then Ho is rejected and Ha accepted. Based on the results of the t test cash turnover, receivables turover and inventories turnover have significant effect between the net profit